Semissíntese de derivados da rotundifolona e análogos - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Rotundifolone is a monoterpenoid ketone derived from piperitenone. It is generally found in species of the genus Mentha and has several proven biological activities, however with divergent results regarding its cytotoxicity. This molecule has been isolated from the essential oil of Lippia pedunculosa leaves with high yield. Its presence and activities are reported in several studies but little has been published about it in the organic synthesis area. This work aims to perform semisynthesis of rotundifolone derivatives and some analogues ((R)-(-)- carvone, (-)-mentone and (R)-(+)-pulegone). The oil constituents and products obtained were separated by CCDP and analyzed by NMR and mass spectrometry. Rotundifolone is identificate as a major compound of essential oil and its presents a [𝛼]20 𝐷 = + 171,4. The reactions were carried out with rotundifolone and its commercial analogues, (R)- (+)- pulegone, (R)-(-)-carvone and (-)-mentone. The reduction with NaBH4 generated the alcohols pulegol and isopulegol, carveol and menthol. Rotundifolone was reduced to rotundifolol a new compound that the epoxy ring is retained. Allyl bromination preferably showed the methyl position over ring substitution, thus generating the derivatives replaced in positions 9 and 10 for bromocarvone, 8 and 9, for bromopulegone, 8 and 9, for bromorotundifolone. Three benzaldoximes were synthesized from the corresponding benzaldehydes and two unpublished izosazoline compounds from the cycloaddition of the latter with rotundifolone.
Semissynthesis of derivatives of rotundifolona and analogues
Keywords: Piperitenona; Citotoxicidade; Lippia pedunculosa; Bromação alílica; Bromorotundifolona; CIÊNCIAS EXATAS E DA TERRA; (+)-rotundifolona; Semissíntese; Redução; Bromação alílica; Cicloadição 1,3 dipolar